The The Effect of The BNI DIVA Application and Digital Competence on Employees' Work Motivation Through Self-Efficacy as an Intervening Variable at BNI Pematangsiantar - Fauziah Ramadayanty Harahap; Yeni Absah; R. Hamdani Harahap (Indonesian Journal Publisher, 2026)
This study examines the effect of the BNI DIVA application and digital competence on employees' work motivation through self-efficacy as an intervening variable at BNI Pematangsiantar. Digital transformation in the banking sector has encouraged the adoption of Artificial Intelligence (AI)-based technology, requiring employees to possess adequate digital competence and self-efficacy in order to remain motivated. This research used an associative quantitative design with a saturated sampling technique covering all 61 employees of BNI Pematangsiantar. Data were collected through a five-point Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) in SmartPLS 3. The results show that the BNI DIVA application and digital competence each have a positive and significant effect on work motivation and self-efficacy, that self-efficacy positively and significantly affects work motivation, and that self-efficacy significantly mediates the effects of both the BNI DIVA application and digital competence on work motivation. These findings confirm that self-efficacy plays a critical intervening role in strengthening the influence of AI-based application usage and digital competence on employees' work motivation.